Improvement of social functioning in patients with first-episode schizophrenia using blonanserin treatment: a prospective, multi-centre, single-arm clinical trial - Gao, Tianqi; Deng, Hong; Sheng, Jianhua; Wu, Bin; Liu, Zhening; Yang, Fude; Wang, Lina; Hu, Shaohua; Wang, Xijin; Li, Haiyun; Pu, Chengcheng; Yu, Xin (Frontiers in Psychiatry, 2024)
Objectives: This clinical trial primarily aimed to investigate the effects of blonanserin on social functioning in patients with first-episode schizophrenia. Methods: In this prospective, multi-centre, single-arm clinical trial study, blonanserin (flexible oral dose ranging from 8mg to 24mg per day) was given 26 weeks. Outcome measures included the Personal and Social Performance (PSP) scale for evaluating social functioning, the Measurement and Treatment Research to Improve Cognition in Schizophrenia Consensus Cognitive Battery (MCCB) for measuring neurocognitive performance, and the Positive and Negative Syndrome Scale (PANSS) for assessing symptom severity. The primary endpoint was social function improvement evaluated by PSP scale at the end of blonanserin treatment. And the secondary endpoint was to validate the efficacy and neurocognitive effects of blonanserin.Adverse drug reactions (ADRs) were also recorded and analysed. Results: A total of 96 patients with first-episode schizophrenia were recruited and proceeded to analysis. Fifty-one participants (53.1%) completed the PSP scale measurements at baseline and week 26. Following 26 weeks of blonanserin treatment, all outcome measurements demonstrated significant improvement during the follow-up period. Notably, PSP scores exhibited a continuous increase up to 68.1% ± 103.7% at the end of the treatment (46.6 ± 14.6 at baseline, 69.4 ± 17.4 at week 26, p<0.001), indicating positive effects on social functioning that were already noticeable by week 8. Conclusion: Blonanserin treatment exhibited favourable effects on social functioning in individuals with first-episode schizophrenia. The results suggest that blonanserin was effective treatment options for patients with schizophrenia encountering functional impairments.